Multidisk Clutch Optimization Using Quantum Annealing - D. John Malcolm; Alexander Roth; Mladjan Radic; Pablo Martin-Ramiro; Jon Oillarburu; Borja Aizpurua; Roman Orus; Samuel Mugel (IEEE Transactions on Quantum Engineering)
In this article, we apply a quantum optimization algorithm to solve a combinatorial problem with significant practical relevance occurring in clutch manufacturing. It is demonstrated how quantum optimization can play a role in real industrial applications in the manufacturing sector. Using the quantum annealer provided by D-Wave Systems, we analyze the performance of the quantum and quantum–classical hybrid solvers and compare them to deterministic- and random-algorithm classical benchmark solvers. The continued evolution of the quantum technology, indicating an expectation for even greater relevance in the future, is discussed, and the revolutionary potential it could have in the manufacturing sector is highlighted.